2014
DOI: 10.3109/17518423.2014.955213
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Alberta Infant Motor Scale (AIMS) to detect developmental delay of gross motor skills in preterm infants: A systematic review

Abstract: Given the evidence, the research supporting the ability of Alberta Infant Motor Scale to diagnose delayed motor development in preterm infants presents limitations. Further studies are suggested in order to avoid the above-mentioned biases to assess the Alberta Infant Motor Scale accuracy in preterm babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
0
13
1
2
Order By: Relevance
“…Characteristically a screening tool should have a high sensitivity, where it is capable of picking up almost all positive cases. Many studies have reported that AIMS is routinely used to detect older children with motor problems early; however, we did not find any studies done on neonates (4,5,6).…”
Section: Figurecontrasting
confidence: 73%
“…Characteristically a screening tool should have a high sensitivity, where it is capable of picking up almost all positive cases. Many studies have reported that AIMS is routinely used to detect older children with motor problems early; however, we did not find any studies done on neonates (4,5,6).…”
Section: Figurecontrasting
confidence: 73%
“…5,9,6 Due to these reasons, AIMS has been widely used as a measure of clinical outcomes and research, both in preterm and term infants around the world. 9,10,13,18 Nevertheless, several studies indicated that AIMS normative data would be inadequate for children of different cultures. 11,15,22,27 One such study by Fleuren et al 21 or international differences.…”
Section: Discussionmentioning
confidence: 99%
“…5,8 AIMS has been used internationally as a clinical or research outcome measure for assessing gross motor abilities of term or preterm infants, although it is a Canadian norm-references measure. [9][10][11][12][13] The validity of the AIMS was obtained for infants in Spain, 12 a South African region, 14 Brazil, 15 Japan, 16 China, 17 and Taiwan. 18 Although AIMS is commonly used in various countries, the question remains as to whether current Canadian norm values represent the AIMS scores of infants with different cultural backgrounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En población pediátrica, se utilizan escalas de medición para la predicción de retrasos en las dimensiones del desarrollo del niño, entre las escalas validas se encuentran la escala abreviada del desarrollo, escala de Alberta, GMFM (Gross motor function measure)-88, GMFM(Gross motor function measure)-66 y Infanib las cuales son capaces de identificar retrasos en el desarrollo y así mismo brindar herramientas de intervención para ayudar a la corrección de las alteraciones producidas para la realización de actividades funcionales en los niños (Almeida, 2008) (Alotaibi, 2014) (Charpak, 2016) (De Albuquerque, 2015 (Dumas, 2015) (Harris S. R., 2010) (Hormiga, 2008) (Ko, 2012) (Liao, 2012) (Lundkvist Josenby, 2009) (Muñoz-Caicedo, 2013 (Snyder, 2008) (Valentini, 2012).…”
Section: Desarrollo Neuromotor E Integridad Sensorialunclassified